Mitigasi yang Diinisiasi Masyarakat Akibat Abrasi di Kawasan Pesisir Kota Semarang - Hanandi Prabowo; Imam Buchori (Jurusan Perencanaan Wilayah dan Kota, 2018)
Coastal area is one area that is prone to the hazard. Coastal areas are vulnerable to environmental changes either due to natural processes or human activities. In carrying out various activities, humans make changes to the environment and natural resources that will affect the environment in coastal areas. Utilization of less ecological principles can reduce the quality of the environment so that it continues with the occurrence of damage to the coastal ecosystems. Abrasion or coastal erosion is considered as hazard to coastal development. The impact of coastal erosion in Semarang city such as mangrove damage, land cover which turn into the sea, and decreased of pond, which would certainly will impact on the economy of coastal communities.Community mitigation efforts in anticipating coastal erosion hazard have been done both with physical development and non-physical efforts in the coastal areas by government and community.This study aims to examine the structural and non-structural forms of mitigation initiated by communities on the affected areas by coastal erosion in Semarang City and the factors that influence it. This research uses quantitative descriptive analysis and logistic regression in the analysis process. Methods of data collection using observations and questionnaires with household observation unit. Observations were made to determine the forms of mitigation conducted by the community then logistic regression analysis was conducted to determine the factors that influence the mitigation.Respondents are people in coastal areas affected by abrasion.The results show there are six forms of mitigation. There are four forms structural mitigation initiated by the community such as construction of seawall, setting-up bamboo spears, construction of breakwater, and mangrove planting. Then there are two forms of non-structural mitigation such as mangrove coastal ecotourism and empowerment of human resources and coastal area management. Based on the logistic regression analysis it is found that the factors which influence community to initiate mitigation are income level, education level, duration of living, and kinship relationship.